Registration of 17 upland cotton germplasm lines with improved resistance to Fusarium wilt race 4 and good fiber quality. Issue 1 (16th November 2022) - Ulloa, Mauricio; Hutmacher, Robert; Zhang, Jinfa; Schramm, TariLee; Roberts, Philip A.; Ellis, Margaret L.; Dever, Jane; Wheeler, Terry A.; Witt, Travis; Sanogo, Soum; Hague, Steve; Keely, Mark P.; et al.
Abstract: With Fusarium wilt ( Fusarium oxysporum f. sp. vasinfectum W.C. Snyder & H.N. Hansen) race 4 (FOV4) formally identified in proximity to the High Plains of west Texas—the largest upland cotton ( Gossypium hirsutum L.) producing region in the United States—the need to develop cultivars resistant to FOV4 has become urgent.  Currently, there are no commercial upland cultivars available claiming FOV4 resistance. Fusarium wilt race 4, a soil‐borne fungus, has affected the cotton crop in the San Joaquin Valley of California for two decades. The primary purpose for the release of the upland PSSJ‐FRU01–PSSJ‐FRU17 (Reg. no. GP‐110–GP‐1126, PI 699966–PI 699982) germplasm lines is to provide cotton breeders with urgently needed sources for FOV4 resistance in upland cotton. The lines were derived from six different cross‐combinations using 10 parental lines with different genetic backgrounds (e.g., 'DES 920' [PI 536522], 'NM12Y1004' [NuMex COT 15 GLS, PI 678371], 'MARS ROSE CLUSTER' [PI 528483], 'AUBURN M' [PI 529214], and 'SA‐3208' [LIAO MIAN 7 HAO]). Several cycles of selection were applied to these developed lines based on an asymptomatic single plant selection after greenhouse FOV4 inoculations or infested field evaluations from F1 to F4 . In 2019–2021 evaluations, germplasm lines showed enhanced resistance to FOV4 with significantly lower percentage mortality and vascular root staining as compared to resistant controls ('Pima‐S6' and 'PHY 881 RF') and improved fiber strength and some long fibers. These released lines will help to reduce the vulnerability of upland cotton to this fungal pathogen and advance efforts to broaden the resistance genetic base which is critical for the upland cotton industry. Core Ideas: Germplasm lines provide urgently needed sources for improving Fusarium wilt race 4 (FOV4) resistance in upland cotton. Germplasm lines increase the upland cotton safety net by reducing vulnerability against FOV4 fungal pathogen. With different genetic background, parents were selected to increase genetic diversity in developed germplasm lines. Lines possess improved resistance to FOV4 when compared to commercial cultivars. This is the first public set of upland germplasm lines with improved FOV4 resistance developed from parents with diverse genetic backgrounds.